2019
DOI: 10.1152/ajprenal.00018.2019
|View full text |Cite
|
Sign up to set email alerts
|

A dual blocker of endothelin A/B receptors mitigates hypertension but not renal dysfunction in a rat model of chronic kidney disease and sleep apnea

Abstract: Obstructive sleep apnea is characterized by recurrent episodes of pharyngeal collapse during sleep, resulting in intermittent hypoxia (IH), and is associated with a high incidence of hypertension and accelerated renal failure. In rodents, endothelin (ET)-1 contributes to IH-induced hypertension, and ET-1 levels inversely correlate with glomerular filtration rate in patients with end-stage chronic kidney disease (CKD). Therefore, we hypothesized that a dual ET receptor antagonist, macitentan (Actelion Pharmaceu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…Our findings of an activation of the endothelin system in fibrotic kidney disease is in accordance with previous reports, which demonstrated either an enhanced ET-1 gene expression [1,16,43,44] or an increased ET A gene expression [9,16] in experimentally induced kidney fibrosis. We now extend these findings by showing the localization of increased ET-1 and ET A gene expression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings of an activation of the endothelin system in fibrotic kidney disease is in accordance with previous reports, which demonstrated either an enhanced ET-1 gene expression [1,16,43,44] or an increased ET A gene expression [9,16] in experimentally induced kidney fibrosis. We now extend these findings by showing the localization of increased ET-1 and ET A gene expression.…”
Section: Discussionsupporting
confidence: 93%
“…ET-1 binds to either ET A -or ET B -R which mainly activate the inositol triphosphate signaling cascade intracellularly [26,50,52]. In damaged kidneys, an increase of ET-1 and ET A -R mRNA expression has been already reported [1,9,33,43,44,65]. An important role of ET-1 in renal fibrosis was elucidated from the finding that transgenic mice overexpressing human ET-1 develop renal abnormalities associated with interstitial fibrosis [25] and that inhibitors of endothelin receptors can attenuate experimentally induced fibrosis [5,45,48].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, as a competitive and specific antagonist for both ET A R and ET B R, bosentan presented an insignificant effect on albuminuria and blood pressure compared with placebo. The insignificant renoprotective effect with bosentan observed in this study is consistent with previous observations that dual ET A / B R blockade has a weaker effect on renal function than selective ET A R blockade 10,27 . As mentioned above, ET A R activation causes vasoconstriction, cell proliferation and extracellular matrix accumulation, whereas ET B R activation promotes antiproliferative and antifibrotic pathways and vasodilation 10,11 .…”
Section: Discussionsupporting
confidence: 91%
“…The insignificant renoprotective effect with bosentan observed in this study is consistent with previous observations that dual ET A / B R blockade has a weaker effect on renal function than selective ET A R blockade. 10,27 As mentioned above, ET A R activation causes vasoconstriction, cell proliferation and extracellular matrix accumulation, whereas ET B R activation promotes antiproliferative and antifibrotic pathways and vasodilation. 10,11 It is possible that the lack of renoprotective effect was attributable to the blockade of ET B Rs to mask ET A protection by diminishing ET B activation of anti-fibrotic and anti-inflammatory pathways.…”
Section: Discussionmentioning
confidence: 98%
“…These proteases are capable of causing pathophysiological activation of the epithelial Na + channel, which can result in reduced Na + excretion, fluid retention, and hypertension (7). A study by Morales-Loredo et al (8) found that the next-generation dual endothelin receptor antagonist macitentan was capable of reducing hypertension but not renal dysfunction in a chronic kidney disease-sleep apnea rat model. From a more molecular perspective, F€ ahling et al (3) verified that annexin-A2 nucleic acid binding occurs following angiotensin II stimulation and may be an important transcriptional regulator of angiotensin receptor signaling.…”
mentioning
confidence: 99%